Effects of Saccharomyces cerevisiae Yeast Supplementation on the Performance and Egg Quality of Laying Hens Feed Low-Dose Aflatoxin B1-Contaminated Diets - Pantaya, Dadik; Ningsih , Niati; Wulandari, Suci (Fakultas Peternakan Universitas Jambi, 2026)
Background: Aflatoxin contamination in poultry feed remains a major challenge due to its adverse effects on productivity and economic performance. Poultry feed with aflatoxin contamination can have harmful effects on chicken production. Purpose: The study was conducted to evaluate the effect of bioactive yeast Saccharomyces cerevisiae (Sc) on reducing the negative effect of diets contaminated under low doses of aflatoxin B1 (AFB1) exposure (30 ppb) on the performance of laying hens. Methods: A total of one hundred, 24-week-old commercial line Hisex brown laying hens were randomly divided into four treatments with five replicates, with five hens in each replicate. The treatments comprised control P0 = basal diet (BD) without Sc and AFB1; P1 = BD + 30 ppb AFB1 without Sc; P2 = BD + 30 ppb AFB1 + 0.5 g Sc/kg diet; and P3 = BD + 30 ppb AFB1 + 1 g Sc/kg diet. The observed variables were 1) Layer performance, 2) the physical quality of eggs, and 3) liver histomorphology, and 4) Relative liver weight (%) and Serum glutamic oxaloacetic transaminase (SGOT)(U/L) value. Results: The results revealed that exposure to AFB1 at 30 ppb had no significant effect on egg production, feed consumption, the feed egg ratio (FER), liver histomorphology, relative liver weight (%), and SGOT liver enzyme activity in laying hens. However, feed contaminated with low doses of AFB1 significantly reduced eggshell thickness, while the supplementation of Sc to the contaminated feed significantly prevented such thinning (P<0.02). Conclusion: The conclusion drawn is that the addition of Sc to feed can counter the negative effect of AFB1 on the egg quality particularly eggshell thickness.